Chloroperoxidase applications in chemical synthesis of industrial relevance - Bhandari, Yogesh; Sajwan, Hemlata; Pandita, Parul; Koteswara Rao, Vamkudoth (Biocatalysis and Biotransformation, 2023)
Biocatalysts can accelerate the catalysis of a chemical reaction that is difficult to synthesize with typical chemical methods. The global enzyme market size is predicted to expand at a CAGR of 6.5% from 2021 to 2028. Enzymatic reactions are highly chemo, regio, and stereoselective and produce various fine chemicals such as drugs, agrochemicals, and fragrance molecules. Peroxidases (PO) (EC 1.11.1.x) are a large class of enzymes that play an important role in various biological processes. Chloroperoxidase (CPO, EC 1.1.1.10) is a versatile fungal haem-thiolate protein that is useful in the asymmetric synthesis of chiral building blocks and has an important role in a number of biological processes. CPO's main biological role is chlorination, although it also catalyses haem PO, catalase (CAT), and reactions similar to cytochrome P450. However, CPO performs both oxidation and stereo-specific halogenation of chemical molecules. The haem and vanadium POs are produced by Caldariomyces fumago, and Curvularia inaequalis, respectively, and are capable of halogenating the flavanones, naringenin, and hesperetin, at C-6 and C-8 in the presence of either Cl- or Br-. In this review, we discussed the various applications of CPO including synthesis of epoxides, drugs, halogenation of thymol, nitriles, the Aza-Achmatowicz reaction, and biomedical applications such as cancer and biosensors. In light of these novel features, we have provided a detailed review of CPOs and their applications in various stereoselective chemical transformations of industrial relevance.
Keywords: active pharmaceutical ingredients; Biotransformation; Caldariomyces fumago; chemo; Chloroperoxidase; regio; stereoselectivity